Lexical cohesion analysis on articles of the Russia-Ukraine conflict in Arabic and English online newspapers - Syofyan Hadi; Hetti Waluati Triana; Tafiati Tafiati; Wartiman Wartiman; Reflinaldi Reflinaldi (Universitas Syiah Kuala, 2024)
Discourse studies on the Russia-Ukraine conflict have been conducted in the past few years, especially in newspapers. Comparative studies on the media in several countries have been widely carried out; however, none so far focused on comparing Arabic and English newspapers. Thus, this article aimed to examine the lexical cohesion of Arabic and English newspapers to identify each newspapers tendency to represent the conflict. Aljazeera and The Guardian newspaper were designated as subjects of the study, in which five opinions published in March 2022 by each newspaper were purposively selected as data sources. Data was collected through internet archival documentation techniques and analysed by referring to the lexical cohesion theory framework proposed by Halliday and Matthiessen (2013). The results showed that repetition was the dominant cohesive device used in Aljazeera, whereas repetition and collocation were the most used lexical cohesion devices in The Guardian. The use of these lexical cohesion devices showed that Aljazeera took a neutral position in representing conflicts and actors. On the other hand, The Guardian tended to side with Ukraine while framing Russia and Putin negatively. Differences in these tendencies were due to the differences in interests. Aljazeera could stay impartial because Qatar had no political interests in the conflict. By contrast, The Guardian was positioning itself against Russia and Putin because Britain had economic and geopolitical interests in the conflict.